Driving Curriculum and Technological Change to Support Writing in the Engineering Disciplines : Final Report. - Calvo, Rafaelo; Howard, Sarah (Office for Learning and Teaching, 2016)
Written communication skills are recognised as essential for all Australian graduates to productively participate in their future work and lifelong learning. In engineering, there are ongoing concerns about discrepancies between students' communication skills and those required in the workplace. Some inroads have been made in the number of academics incorporating written tasks into their curricula and students are exhibiting improved writing skills. Yet, many academics remain reluctant and resistant to change and we are far from the writing across the curricula ideal. The challenges are a combination of technical, disciplinary and institutional risks. This project involved a collaboration across four universities to develop an integration model addressing these risks through the use of online writing tools and communication, to support and sustain the integration of written tasks in undergraduate engineering and drive curriculum innovation. The outcome of project was an integration model supporting development of academics' capacity to integrate written tasks and improvement in students' written communication skills.